Cli-fi : une mosaïque globale - Carl Abbott; Lieven Ameel; Simon Bréan; Sébastien Fevry; Irène Langlet (ReS Futurae)
Should we define climate fiction, cli-fi ? Or rather experience it and practice it, through creation as well as in criticism and theory ? The scientific committee of the symposium The City in Climate Fictions (2021) took part in the exercise. Five brief variations are proposed : a) on the narrative forms and the questions they raise by embodying them in the stories ; b) on the emotional turn of emergency in cli-fi ; c) on the scales of action it can express ; d) on the intermedial interlinking it generates (with the help of a wild boar) ; e) on the popular or spontaneous critical categorization it manifests.